2022
DOI: 10.3390/catal12111394
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Simple Microwave-Assisted Synthesis of Benzoxazoles Catalyzed by [CholineCl][Oxalic Acid]

Abstract: Microwave irradiation has been used to enhance the reaction yields and selectivities for organic transformation. In this paper, microwave irradiation (MW) was investigated for the environmentally benign synthesis of benzoxazoles through the cyclization of 2-aminophenols and benzaldehydes using deep eutectic solvent (DES) as a catalyst. The [CholineCl][oxalic acid] was easily synthesized from choline chloride with oxalic acid and used without further purification. [CholineCl][oxalic acid] catalyzed the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…2. According to the data provided by the TGA, the mass does not change much (approximately 10%) even at the first thermal decomposition step when the temperature is raised to 130 °C; nevertheless, previous work [27,28,30] has shown that when the temperature is increased from 200 °C to 300 °C, this fully disintegrates. At the final thermal degradation step, [CholineCl][Citric acid] completely decomposed in the temperature range from 300 °C to 450 °C, while the structure of [CholineCl][Oxalic acid] completely decomposed above 300 °C.…”
Section: Characterization Of Dessmentioning
confidence: 87%
See 1 more Smart Citation
“…2. According to the data provided by the TGA, the mass does not change much (approximately 10%) even at the first thermal decomposition step when the temperature is raised to 130 °C; nevertheless, previous work [27,28,30] has shown that when the temperature is increased from 200 °C to 300 °C, this fully disintegrates. At the final thermal degradation step, [CholineCl][Citric acid] completely decomposed in the temperature range from 300 °C to 450 °C, while the structure of [CholineCl][Oxalic acid] completely decomposed above 300 °C.…”
Section: Characterization Of Dessmentioning
confidence: 87%
“…The peak at 1720 cm −1 is typical of the stretching vibrations of C=O. In addition, a wide bulb absorption band characteristic of the O-H group is observed at 3354 cm −1 [27]. Therefore, [CholineCl][Oxalic acid] was synthesized from choline chloride and oxalic acid in a 1:1 ratio; the FT-IR results showed the presence of characteristic oscillations for both components.…”
Section: Characterization Of Dessmentioning
confidence: 99%
“…With regard to the selectivity, it was determined for the two final products for which the best yields were attained and their intermediates, using HRMS-ESI (Figure S6). The product ratio of the (E)- [7], for which selectivities of up to 1/99 were attained in the case of some benzoxazoles.…”
Section: Catalytic Conditions and Yieldsmentioning
confidence: 99%
“…A well-known method for the preparation of such benzoxazoles and benzimidazoles is the condensation-aromatization of 2-aminophenol and 2-phenylenediamine, respectively, with aldehydes using Brønsted-Lowry acid catalysts [5]. Among the potential catalysts for this reaction process, the ones that have received the most attention have been the taskspecific ionic liquids [6], the Brønsted acidic ionic liquid gels [5], and the [CholineCl][oxalic acid] deep eutectic solvent (DES) [7].…”
Section: Introductionmentioning
confidence: 99%